DNA Methylation and Protein Markers of Chronic Inflammation and Their Associations With Brain and Cognitive Aging. (7th December 2021) - Conole, Eleanor L.S.; Stevenson, Anna J.; Muñoz Maniega, Susana; Harris, Sarah E.; Green, Claire; Valdés Hernández, Maria del C.; Harris, Mathew A.; Bastin, Mark E.; Wardlaw, Joanna M.; Deary, Ian J.; Miron, Veronique E.; Whalley, Heather C.; et al.
Abstract : Background and Objectives: To investigate chronic inflammation in relation to cognitive aging by comparison of an epigenetic and serum biomarker of C-reactive protein and their associations with neuroimaging and cognitive outcomes. Methods: At baseline, participants (n = 521) were cognitively normal, around 73 years of age (mean 72.4, SD 0.716), and had inflammation, vascular risk (cardiovascular disease history, hypertension, diabetes, smoking, alcohol consumption, body mass index), and neuroimaging (structural and diffusion MRI) data available. Baseline inflammatory status was quantified by a traditional measure of peripheral inflammation—serum C-reactive protein (CRP)—and an epigenetic measure (DNA methylation [DNAm] signature of CRP). Linear models were used to examine the inflammation–brain health associations; mediation analyses were performed to interrogate the relationship between chronic inflammation, brain structure, and cognitive functioning. Results: We demonstrate that DNAm CRP shows significantly (on average 6.4-fold) stronger associations with brain health outcomes than serum CRP. DNAm CRP is associated with total brain volume (β = −0.197, 95% confidence interval [CI] −0.28 to −0.12, p FDR = 8.42 × 10 −6 ), gray matter volume (β = −0.200, 95% CI −0.28 to −0.12, p FDR = 1.66 × 10 −5 ), and white matter volume (β = −0.150, 95% CI −0.23 to −0.07, p FDR = 0.001) and regional brain atrophy. We also find that DNAm CRP has an inverse association with global and domain-specific (speed, visuospatial, and memory) cognitive functioning and that brain structure partially mediates this CRP–cognitive association (up to 29.7%), dependent on lifestyle and health factors. Discussion: These results support the hypothesis that chronic inflammation may contribute to neurodegenerative brain changes that underlie differences in cognitive ability in later life and highlight the potential of DNAm proxies for indexing chronic inflammatory status. Classification of Evidence: This study provides Class II evidence that a DNAm signature of CRP levels is more strongly associated with brain health outcomes than serum CRP levels.